HBeAg-positive patients with HBsAg < 100 IU/mL and negative HBV RNA have lower risk of virological relapse after nucleos(t)ide analogues cessation - Xie, Yandi; Li, Minghui; Ou, Xiaojuan; Zheng, Sujun; Gao, Yinjie; Xu, Xiaoyuan; Yang, Ying; Ma, Anlin; Li, Jia; Huang, Yuan; Nan, Yuemin; Zheng, Huanwei; et al. (Journal of gastroenterology, 2021)
Background Nucleos(t)ide analogues (NAs) cessation is not widely practiced and remains a controversial, but highly relevant subject in patients infected with hepatitis B virus (HBV). We aimed to explore the related factors for safe NAs cessation. Methods This is a multicenter prospective cohort study. Overall, 139 initially HBV e antigen (HBeAg)-positive patients meeting the stopping criteria were included in 12 hospitals in China. Enrolled patients ceased NAs and were followed up every 3 months for 24 months or until clinical relapse (CR). Results The 24 month cumulative rates of virological relapse (VR), CR, HBeAg reversion and HBV surface antigen (HBsAg) loss were 50.4, 24.5, 11.5 and 9.4%, respectively. Patients with end of treatment (EOT) HBsAg  < 100 IU/mL plus negative HBV RNA had the lowest 24 month cumulative VR rate (5 vs 58%, p < 0.001). EOT HBsAg  ≥ 2 log 10 IU/mL [odds ratio (OR) = 6.686 , p = 0.006], EOT positive HBV RNA (OR = 3.453 , p = 0.008) and EOT hepatitis B core-related antigen (HBcrAg)  ≥ 4log U/mL (OR = 3.702 , p = 0.002) were found to independently predict the risk of VR. To predict VR, the area under the receiver-operating characteristic (AUROC) value of the EOT HBsAg  < 100 IU/mL plus EOT HBV RNA negative was 0.698 ( p < 0.001), which was higher than other parameters alone or combinations. Conclusions NAs cessation is suitable only for a small and selected patients. An EOT HBsAg  < 100 IU/mL and EOT negative HBV RNA identified a patient with low risk of off-treatment VR.